1998
DOI: 10.1177/095632029800900607
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Picornavirus Activity of Synthetic Flavon-3-yl Esters

Abstract: Members of the family Picornaviridae, which comprise rhinoviruses and enteroviruses, are responsible for several human diseases. It is estimated that over 100 serotypes of human rhinoviruses (HRV) cause approximately half of all cases of the common cold. Also, poliomyelitis still represents a relevant health problem in some countries of the world, despite a dramatic decrease in its incidence as a result of intensive vaccination programmes in developed countries. There therefore exists a need to search for effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 24 publications
0
13
1
Order By: Relevance
“…Flavonoids as well as sesquiterpenes with anti-herpesvirus and anti-influenzavirus activity have been described (Nagai et al, 1995;Hayashi et al, 1996;Shahat et al, 2002;Chiang et al, 2003;Krawczyk et al, 2003). Although, flavonoids may inhibit picornaviral replication (De Meyer et al, 1991;Conti et al, 1998;Semple et al, 1999), no anti-CVB3 activity of Inula confertiflora extracts was found. Plants containing flavonoids in a sufficiently large concentration were shown to be effective in topical treatment of skin or mucous membrane inflammation (Hoermann and Korting, 1994;Asres et al, 2000).…”
Section: Discussionmentioning
confidence: 64%
“…Flavonoids as well as sesquiterpenes with anti-herpesvirus and anti-influenzavirus activity have been described (Nagai et al, 1995;Hayashi et al, 1996;Shahat et al, 2002;Chiang et al, 2003;Krawczyk et al, 2003). Although, flavonoids may inhibit picornaviral replication (De Meyer et al, 1991;Conti et al, 1998;Semple et al, 1999), no anti-CVB3 activity of Inula confertiflora extracts was found. Plants containing flavonoids in a sufficiently large concentration were shown to be effective in topical treatment of skin or mucous membrane inflammation (Hoermann and Korting, 1994;Asres et al, 2000).…”
Section: Discussionmentioning
confidence: 64%
“…236 Several synthetic flavonoid and isoflavonoid derivatives were evaluated for their potential antipicornavirus activity. [237][238][239][240][241] In general, flavanones proved to be less active against picornaviruses than flavones, and 3-substitution appeared to be compulsory for potent activity. 242 Among the 3-substituted analogues, the presence of a 3-hydroxy group resulted in increased activity against poliovirus, whereas a 3-methoxy group proved beneficial for the activity against HRV-1B.…”
Section: -Furylmercury Chloride (2-fmc)mentioning
confidence: 94%
“…On the other hand, esterification of the 3-hydroxy group with bulky substituents increased toxicity without significantly improving antiviral activity. 237 The synthesis of 2-styrylchromones as vinylogues of flavones, led to the identification of some analogues with antiviral activity against rhinoviruses (with EC 50 values for HRV-14 of 1.33 mM for the best compound in this series). 239 As expected, introduction of a methoxy-or hydroxyl group at position 3 of these 2-styrylchromones led to more potent analogues, with the best compound (''compound 4h'') ( Fig.…”
Section: -Furylmercury Chloride (2-fmc)mentioning
confidence: 99%
“…Flavonols along with other flavonoids and polyphenolic compounds influence the immune system and inflammatory cells (Middleton et al, 2000) and have antimicrobial properties (Conti et al, 1998;Middleton et al, 2000;Puupponen-Pimiä et al, 2001). The most convincing evidence on the efficacy of vitamins in CC treatment or prevention concerns people whose immune system may not function optimally or who are under exceptional stress (Hemilä et al, 2002(Hemilä et al, , 2004Meydani et al, 2004).…”
Section: Discussionmentioning
confidence: 99%